Optimalisasi Proses Pembelajaran Mahasiswa PPG Seni Budaya Melalui Implementasi Edukit Berbasis Interactive Surface - Iriaji; Titi Rahayuningsih; Yuliati; Eka Putri Surya; Alby Aruna; Adinda Marcelliantika (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to optimize the learning process of PPG Arts and Culture students through the implementation of Interactive Surface-based education. The methodology used includes needs analysis, design and development of education, as well as evaluation of the effectiveness of its implementation. This education is designed to provide a more interactive and immersive learning experience, using Interactive Surface technology that allows direct manipulation of learning content. The research results showed a significant increase in student engagement and understanding of the learning material. Evaluation through surveys and in-depth interviews confirms that this education is effective in supporting more adaptive and innovative learning strategies. This research makes an important contribution to the development of modern learning tools that are relevant to today's educational needs.